Conservation tillage-based Arundo donax agro-geotextiles enhance productivity and profitability of sloping croplands in the Indian Himalayas by reducing soil erosion and improving soil organic carbon - Singh, R. J.; Kumar, Gopal; Sharma, N. K.; Deshwal, J. S.; Mishra, M.; Roy, P.; Bhattacharyya, R.; Madhu, M. (Elsevier, 2025)
Very few soil erosion studies have investigated the effectiveness of conservation tillage (CT)-based agrogeotextiles (AGTs) on rainfed sloping croplands of the Indian Himalayan Region (IHR) for intensifying unremunerative double cropping (maize-wheat) to sustainable remunerative triple cropping (maize-pea-wheat). This study assessed surface runoff, soil, and nutrient losses during the rainy season in maize crops to evaluate the impact of eight conservation practices on post-rainy season soil moisture content, productivity, and profitability of the crop rotation, and soil organic carbon (SOC) accumulation over a six-year period (2017–2023) on a 4% sloped natural runoff gauge plots (100 × 20 m2 ). The conservation practices involved a combination of rainfed maize-wheat and rainfed maize-pea-wheat crop rotations, utilizing two thicknesses (5 cm and 10 cm) and two configurations (0.5 m and 1.0 m vertical intervals) of Arundo donax (AD)-agro-geotextiles (AGTs), with comparisons drawn against the standard farmers’ practice of bench terraces (BT). In the treated CT fields, the highest amounts of residues (6.0–7.1 t ha- 1 ) were recycled by applying 5 and 10 cm thick AD-AGTs at a 0.5 m vertical interval (VI). Approximately 1100–1300 mm of rainfall per hectare per year was retained as soil water, and soil erosion decreased by 80–90% in the treated AD-AGT CT fields compared to the non-treated CT fields, which experienced a loss of 8.5 tonnes per hectare per year of soil. In the AD-AGT CT fields, the highest wheat equivalent yields (12.0–13.6 t ha- 1 year- 1 ), profits (2332–2477 US$ ha- 1 year- 1 ), and SOC build-up (1.16–1.20%) were recorded. In the treated fields, an average of 32–108 kg organic carbon, 3–6 kg nitrogen, 1–3 kg of phosphorus, and 8–37 kg potassium per hectare per year were retained, preventing their loss as pollutants through surface runoff water. The research provided scientific evidence indicating that triple cropping of maize-pea-wheat in a pure rainfed condition of IHR can be achieved without compromising wheat yields, provided that farmers apply CT-based AD-AGTs at the appropriate rate and configuration, i.e., emplacement of 5 cm thick biomass @ 1.1 t ha- 1 on a 0.5 m vertical interval. From a sustainable practice point of view, the study proposes a valorization for AD biomass that contains no economic value. Future soil and water conservation research should examine the impacts of AD-AGTs on soil and water conservation across a diverse range of rainfall and field slope conditions.